Proposed Mechanisms of Change in Arts-based Psychotherapies - Gerge, Anna; Hawes, Jane; Eklöf, Lotti; Pedersen, Inge Nygaard (Voices: A World Forum for Music Therapy, 2019)
The effectiveness of the arts-based psychotherapy methods may rely on offering tools for preverbal implicit processing, especially in work with traumatized clients. This can enhance clients’ self-soothing capacities, activate flow experiences in line with positive psychology, and change inner working models through memory reconsolidation. The arts-based psychotherapies offer expanded Windows of Tolerance through dual awareness, and concretizes the psychotherapist’s care in the therapeutic relationship, in line with psychodynamic psychotherapy. These methods activate the innate human ability to express and experience creativity, including beauty and awe. The arts in therapy offer a creative space of play where a new reality may be constructed and shared. The interventions are proposed to offer more than plain cognitive restructuring and behaviour activation (although they may lead to additional changes in these parameters). The clinical usefulness of the arts-based methods is reflected in relation to traumatized clients’ opinions of what has helped them. The potentially effective mechanisms in the arts-based psychotherapies ought to be further investigated in clinical work and research processes, thus, promoting the methods’ abilities to enhance clients’ well-being and change capability. List of abbreviations: ASC altered state of consciousness; AT art therapy; BMGIM Bonny Method of Guided Imagery and Music; CBT cognitive behavioural therapy; DMN default mode network; EMDR Eye Movement Desensitization and Reprocessing; AMT active music therapy; MT music therapy; PDT psychodynamic psychotherapy; PTSD posttraumatic stress disorder; RCT randomised controlled trial; RMT receptive music therapy; GrpMI Group Music and Imagery; WoT window of tolerance